„Poczta literacka” by Wisława Szymborska – structure and pragmatics - Wojciechowska, Anna (Papers in Linguistics, 2023)
The paper aims to examine Wisława Szymborska’s texts published in a weekly „Życie Literackie”. From 1960 to 1968 a future Nobel Prize in Literature Laureate was a co-editor of a column called „Poczta literacka”. Szymborska evaluated readers’ literary attempts sent in the letters to the editor. The objective of the study is to investigate the structure along pragmatic aspects of these little-known Szymborska’s texts, and to which genres’ conventions they refer to. The method involves Maria Wojtak’s approach towards genre analysis. Findings indicate that: 1) “Poczta literacka” as a column has a clear and stable genre pattern (three fixed components, understandable rules for writing titles and segmentation); 2) The sender can express herself freely in the section edited by Wisława Szymborska. In addition, the conventions of two genres are visible in that part, i.e. the response to the letter to the editor, and the editor’s advice.